Water Warriors Living Lab: Towards an integrated “Heartware - Hardware – Software” Approach to Water Management - Mohamad, Zeeda Fatimah; Kadir, Siti Norasiah Abd; Nasaruddin, Affan; Zuki, Fathiah Mohamed; Hussein, Hazreena; Abdullah, Nor Aishah; Sulaiman, Abdul Halim; Yahya, Sharifah Noor Nazim Syed; Borhan, Mohammad Zainuddin; Mohd Ruslan, Mohd Ramzi; Isa, Nordiana Mohd (Journal of Sustainability Perspectives, 2022)
This paper presents the experience of the Water Warriors Living Lab, a bottom-up sustainable campus action research initiative in applying the integrated ‘Heartware - Hardware – Software’ approach for water management at the University of Malaya since the year 2013. It advances the proposition that a heartware approach is needed to enhance campus sustainability efforts, in addition to the more strategic hardware and software approaches. The paper describes how the Water Warrior’s experience in applying the heartware approach has been a strengthening factor in resolving water conservation issues at the university (specifically in lake management), and discusses important lessons learned to date. Our theoretical and empirical insights can hopefully provide renewed appreciation on how local, organic and humanistic factors can be essential ingredients for the long term ‘sustainability’ of campus sustainability efforts.Keyword: Campus sustainability, living lab, water management, heartware, bottom-up